Spatial Visualization Skills of Student Teacher Applicants : A pilot Study in the Finnish CDT Teacher Education Admissions - Lehtinen Rauli; Huhtala Mikko; Lindfors Eila (Universitetsbiblioteket OsloMet, 2022)
Problem-solving is a key element in design and engineering processes for finding answers to challenges and open problems. The use of spatial visualization skills is part of problem-solving in terms of transforming ideas into 2D or 3D form and transferring this thinking into practice in a practical hands-on process. Spatial visualization seems to play a key role in the design, engineering and production processes as well as in various professions. Spatial visualization skills can be considered as an important part of teachers’ multidimensional professional competence as they teach students and guide and tutor their hands-on projects. While educating teachers, it would be important to know the levels of the student teachers’ spatial visualization skills to consider its role in courses and even in admissions. However, there are no existing studies on spatial visualization skills of student teacher applicants. To address this research gap, we pose the following research question: What is the level of spatial visualization skills of student teacher applicants in craft, design and technology teacher education admissions? The data, analyzed with document analysis, includes student teacher applicants' performance in a spatial visualization test (N=89, three tasks) as part of Finnish craft, design and technology teacher education admissions. According to the results, four of the five applicants performed on a good level whilst only four per cent of applicants performed weakly. Since spatial visualization skills can be trained, it is important to recognize student teachers’ weak performance so that it can be enhanced in various courses. This study is part of a larger problem-solving skills evaluation project in CDT teacher education admissions